Infective complications of tattooing and skin piercing - Ahmed Messahel; Brian Musgrove (Elsevier, 2009)
Summary: Body piercing appears to be gaining popularity and social acceptance. With the increase in the number of piercings and tattoos, it is likely that health care providers may see an increase in the complications resulting from these piercings. These may include the transmission of hepatitis viruses and bacteria at the time of the piercing or in the course of wound care. We review the infectious complications that have resulted from body piercing and tattooing that has been documented in the medical literature. Keywords: Tattooing, Skin piercing, Body piercing